Evaluation of the level of secretory immunoglobulin A and salivary pH with regard to the intensity of dental caries in preschool children subjected to topical application of fluoride - Kowalik, Tomasz; Kujawiak, Magdalena; Grzegorczyk, Janina; Szczepańska, Joanna (Journal of Stomatology, 2015)
Introduction. As the presence of Streptococcus mutans is an etiological factor common to different courses of dental caries, it can be assumed that secretory IgA may be one of the important factors of susceptibility to dental caries. The buffer function of saliva allows an acid– alkaline balance conditioning to be maintained at an optimal pH value. Aim of the study. To assess levels of immunoglobulin A in saliva and pH values with regard to the intensity of dental caries in pre-school children subjected to fluoride varnish application. Material and methods. Saliva was obtained from 121 children aged 4 – 6 years. The patients were divided into three groups based on dmft index: Group I was caries free (dmft = 0), Group II displayed a small number of cavities (dmft ≥ 1 and ≤ 2), and Group III displayed a high intensity of caries (dmft ≥ 3). The sIgA levels and pH of each group were assessed before and after fluoride varnish application. Results. A significantly positive correlation was found between the dmft index and the level of salivary secretory IgA after fluoride varnish application (p = 0.02). A correlation was found between the dmft index and salivary pH values: increased pH was seen at lower dmft values, but this was not statistically significant. A significantly positive correlation was observed between pH and sIgA concentration in saliva, before (p = 0.000) and after fluoride varnish application (p = 0.03). Conclusion. The present study demonstrates that higher levels of secretory IgA in saliva are associated with higher caries experience, especially in children with high dmft values. This may suggest that immunoglobulin A plays a significant, though not entirely understood, role in the carious process.